Optimal Reconstruction After Laparoscopic Distal Gastrectomy: A Single-Center Retrospective Study. (8th March 2022) - Yan, Yongjia; Wang, Daohan; Liu, Yubiao; Lu, Li; Wang, Xi; Zhao, Zhicheng; Li, Chuan; Liu, Jian; Li, Weidong; Fu, Weihua
Objectives: Although laparoscopic distal gastrectomy has been widely used for distal gastric cancer, the best functional reconstruction type has not yet been established. Based on previous experience, we propose a modified uncut Roux-en-Y anastomosis. This study aimed to compare the outcomes of different intracorporeal anastomoses after laparoscopic distal gastrectomy. Methods: From April 2015 to August 2020, the data of 215 patients who underwent laparoscopic distal gastrectomy was collected. The patients were divided into 4 groups according to the digestive tract reconstruction method, Billroth-I, Billroth-II, Roux-en-Y, and the modified uncut Roux-en-Y. Clinicopathologic characteristics, surgery details, short-term outcomes, and postoperative nutritional status were analyzed. Results: The operation time of Billroth-I anastomosis was significantly shorter (216.2 ± 25.8 min, P < .001) than that of other methods. There was no difference in postoperative complications and OS among the 4 reconstruction methods. The incidences of esophagitis, gastritis, and bile reflux were significantly lower in the Roux-en-Y and uncut Roux-en-Y group (P < .001) 1 year after surgery. And the postoperative albumin and PNI levels in uncut Roux-en-Y group were higher than those in other groups(P < .05). On multivariate analysis, age and reconstruction type were independently related to esophagitis, gastritis, and bile reflux. Serum albumin and the prognostic nutritional index were significantly higher in the uncut Roux-en-Y group than other groups (P < .05). Conclusions: All 4 reconstruction techniques are feasible and safe. The Roux-en-Y and uncut Roux-en-Y are superior to Billroth-Ⅰ and Billroth-Ⅱ+Braun in terms of reflux esophagitis, gastritis, and bile reflux. Uncut Roux-en-Y may result in better PNI than the others.